2023
DOI: 10.1177/1098612x221145499
|View full text |Cite
|
Sign up to set email alerts
|

Can cat caregivers reliably assess acute pain in cats using the Feline Grimace Scale? A large bilingual global survey

Abstract: Objectives This study aimed to investigate if cat caregivers could reliably assess acute pain using the Feline Grimace Scale (FGS), and if participant demographics could affect scores. Methods An online survey in English and Spanish was advertised by International Cat Care and other platforms (March–May 2021) using convenience sampling. Eligible participants were caregivers >18 years old and non-veterinary health professionals. Participants and a group of eight veterinarians scored 10 images of cats with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 34 publications
1
26
1
Order By: Relevance
“…17 Finally, our classification for ICC values is more conservative than the one used by Altman (<0.2 = poor; 0.21-0.4 = reasonable; 0.41-0.60 = moderate; 0.61-0.80 = good; and 0.81-1.0 = very good), 23 which may contribute to different interpretations of our results and the use of the FGS in the clinical setting. 9 The intrarater reliability of the FGS total ratio scores in kittens was good to excellent, which was similar to previous studies with images from adult cats, when ICCs from the FGS total ratio scores from veterinarians were excellent. 5,10 Orbital tightening and ear position ranged from moderate to excellent, muzzle tension ranged from moderate to good, whiskers position was moderate and head position ranged from good to excellent.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…17 Finally, our classification for ICC values is more conservative than the one used by Altman (<0.2 = poor; 0.21-0.4 = reasonable; 0.41-0.60 = moderate; 0.61-0.80 = good; and 0.81-1.0 = very good), 23 which may contribute to different interpretations of our results and the use of the FGS in the clinical setting. 9 The intrarater reliability of the FGS total ratio scores in kittens was good to excellent, which was similar to previous studies with images from adult cats, when ICCs from the FGS total ratio scores from veterinarians were excellent. 5,10 Orbital tightening and ear position ranged from moderate to excellent, muzzle tension ranged from moderate to good, whiskers position was moderate and head position ranged from good to excellent.…”
Section: Discussionsupporting
confidence: 87%
“…5 The FGS has demon strated validity and reliability in various acute painful conditions, 5,8 when evaluated using realtime or image assessment, 6 and when used by individuals with differ ing levels of expertise, including cat caregivers. 9,10 Although some of these assessment tools have gone through extensive validation in adult cats, none have been uniquely validated in kittens. Nonetheless, early age neutering (⩽4 months of age) is now common prac tice in feline medicine and is supported by organizations such as the International Society of Feline Medicine for optimal health, social development and population con trol.…”
Section: Introductionmentioning
confidence: 99%
“…14 Another similar study aimed to investigate the effect of participant demographics on cat caregivers' reliability in assessing acute pain using the FGS. 15 This study also showed that FGS scores had good reliability when used by cat caregivers, regardless of demographic variables, demonstrating the potential applicability of the instrument to improve feline pain management and welfare worldwide. 15 Providing a clear explanation of how to identify signs of pain is given before hospital discharge, cat owners can reliably assess behavioural changes associated with acute pain during the postoperative period Following on from these studies, Hillen and colleagues' study 9 not only rigorously adheres to scientific methodology but also recognises the practical importance of involving cat owners in assessing their pets' pain experience.…”
Section: What You Need To Knowmentioning
confidence: 52%
“…Surgery, pain management, and anesthesia are fundamental areas of small animal veterinary services that involve the collaboration between veterinarians and pet caregivers for adequate patient care. The experiences and perceptions of pet caregivers play an invaluable role in postoperative care, pain management, and evaluation of the Quality of Life (QoL) of their pets [ 1 , 2 ]. Therefore, a major responsibility of veterinary healthcare professionals is to equip the caregivers with the ability to recognize and prevent pain, and milestones related to postoperative care, making client communication and education the cornerstone of effective veterinary services.…”
Section: Introductionmentioning
confidence: 99%